PTU-101 Drugs used in the treatment of fistulae in Crohn's disease preserve mesenchymal stem cell survival. (28th May 2012) - Meran, L; Rashidi, H; Jones, R; Rose, F; Shakesheff, K; Hawkey, C
Abstract : Introduction: Mesenchymal stem cells (MSCs) may enhance tissue healing in fistulae of Crohn's disease, owing to their multilineage differentiation and immunosuppressive capacity. They are currently under investigation in clinical trials in patients with fistulae, whether cryptoglandular in origin or associated with Crohn's disease. Little is known about the interaction of MSCs with drugs used in the treatment of fistulae in Crohn's disease. We demonstrate here that on daily exposure to antibiotics commonly used in the management of fistulae (ciprofloxacin and metronidazole), as well as anti-TNFα (infliximab), mesenchymal stem cell retain their proliferation and differentiation capacity. Methods: Cultured human bone marrow derived MSCs were plated at a density of 5×10 4 cells per square centimeter in 24 well plates and allowed to adhere overnight. Cells were exposed to a range of daily doses of ciprofloxacin, metronidazole (0.1 μg/ml–30 μg/ml) and infliximab (1 μg/ml–500 μg/ml) for a 6-week period. MSC morphology was assessed daily and differentiation capacity into adipocyte, osteocyte and chondrocyte lineages was studied after exposure to the drugs. MSC survival was assessed at 6 weeks using Annexin-V Apodetect assay followed by FACS analysis. Cell survival was expressed as percentages of cells that were negative for Annexin-V and propidium iodide staining. Analyses were performed using the SPSS statistical package (V. 19.0). Results: MSCs exposed to a range of concentrations of ciprofloxacin, metronidazole and infliximab daily, consistently displayed a normal morphology as assessed by light microscopy. Following exposure of these drugs, differentiation into adipocyte, osteocyte and chondrocyte lineages was conserved. In the absence of drugs, mean survival (±SD) of MSCs was 81.8 ±8.6%. In the presence of ciprofloxacin, mean survival of MSCs was generally increased compared to control cells, significantly so at the highest concentration of 30 μg/ml: 90.1% (p<0.05). By contrast, with metronidazole and infliximab there was no suggestion of a change in survival level, when compared to control cells at any of the concentrations used. Conclusion: This study demonstrates that, in vitro, morphological characteristics as well as the proliferation and differentiation capacity of MSCs is preserved in the presence of ciprofloxacin, metronidazole and infliximab. These findings are important in the consideration of the combination of MSCs with antibiotics and anti-TNFα therapy and will inform subsequent studies to optimise drug and cell delivery. Competing interests: None declared.